(untitled) (Foro de Educacion, 2024)
This study examines the role of soft skills training in improving the employment prospects of young professionals, addressing the growing concern about the mismatch between graduates’ competencies and labor market demands. Despite employers prioritizing interpersonal skills like communication, adaptability, and teamwork, many educational institutions continue to focus primarily on technical knowledge, neglecting soft skills development. Using a qualitative systematic literature review guided by the PRISMA framework, the study synthesizes findings from 12 peer-reviewed studies, revealing that well-designed, context-specific soft skills training programs significantly enhance job readiness, retention, and long-term career growth. However, challenges such as inconsistent delivery, ineffective assessment, and misalignment with employer expectations persist across educational systems. The study emphasizes the need to embed soft skills into formal curricula and institutional strategies, calling for pedagogical reforms and employer-integrated approaches to improve graduate employability in a rapidly changing global workforce.